AN ANALYSIS OF THE TRANSLATION OF THE POEM “A DIRGE” BY CHRISTINA ROSSETTI INTO “SEBUAH RATAPAN” BY M. AAN MANSYUR - Sascia, Bernadeth Dwi; Ananda, Dwi Meisyitah; Valentino, Yosafat Barona (Prologue: Journal on Language and Literature, 2025)
Literary works refer to books and writings with distinctive reason, emotion, and imagination characteristics. Poetry is a literary work that is a means for a poet to express the contents of his/her thoughts and feelings by prioritizing the aesthetics of language that is structured in such a way. This study analyzes poetry as a literary work that is transferred from the source language (SL) to the target language (TL), or what is known as poetry translation. This study aims to analyze M. Aan Mansyur’s translation of the poem “A Dirge” by Christina Rossetti. This study uses a qualitative descriptive method because the data is compared and described in writing and content analysis. The data sources are a translation of the poem “Sebuah Ratapan” by M. Aan Mansyur and the original poem in English. This analysis results from Newmark's translation method and Lefevere's poetry translation strategy, showing that free and rhymed poetry translation strategies dominate poetry translation texts.